“Dem sey mi mad”: a scoping review of the attitudes and beliefs of English-speaking Afro-Caribbeans about psychosis - Knight, Sommer; Yang, Xin Qiang; Jarvis, G. Eric (Frontiers in Psychiatry, 2024)
Introduction The mental health disparities suffered by the English-speaking Afro-Caribbean diaspora living with psychosis in North America and the United Kingdom have been well described for decades, but the root causes of these disparities remain poorly understood. Part of the problem may be that the attitudes and beliefs of Caribbean communities regarding psychosis have never been systematically assessed. Such an inquiry could lay the foundation for changes to how psychiatric services for psychosis are implemented with migrant Caribbean communities. The ideal would be a re-design of services, or cultural adaptation of care, based on input from community members, patients, and their families, with the hope that disparities of care would be reduced or eliminated as clinicians co-create interventions that are more appropriate and acceptable to Caribbean people. To lay the groundwork of such an important endeavor, we investigated the shared attitudes, beliefs, experiences, practices, and traditions of English-speaking Afro-Caribbean people in relation to psychosis and psychiatric care. Methods We conducted a scoping review by searching Medline, PsychINFO and Scopus, reviewing 764 articles, and selecting 220 for thematic content analysis. Results We highlighted the heterogeneity in the Caribbean diaspora living in North America and the UK. Five principal themes emerged: (1) The enduring effects of colonialism on the psychiatric care of Afro-Caribbean migrants; (2) The effects of adaptation to migration on the experience of psychosis; (3) Pervasive cultural mistrust of psychiatry and mental health institutions; (4) A collective approach to life; and (5) The role of religion and spirituality in the understanding of psychosis. Conclusion Historical, sociocultural, and geopolitical themes characterize the English Afro-Caribbean experience of psychosis and inform culturally adapted clinical interventions for patients with psychosis and their families. Careful attention to these adaptations will reduce clinical bias and misdiagnosis, optimize adherence to treatment, engage patients and families in recovery, and ultimately, reduce treatment disparities while empowering Afro-Caribbean people and their communities. By bringing forward the themes in this chapter, individual clinicians will be given tools to change how they work with Caribbean people with psychosis in addition to laying the foundation for higher order changes in the mental health professions and society as a whole.